Effect of Textual and Graphic Areas in Advertisements on Consumers: An Eye-Tracking Enquiry for Digital Ad Images - Mihir Belgaonkar, Dr. Preetha Menon (International Journal of Advanced Science and Technology, 2020)
Advertisement is effective for a brand when it leads to brand awareness, which in turn translates into sales. Every day, consumers are bombarded with various advertising creatives by companies, which differ in their creative approach. Creatives can be text heavy, imagery heavy, or balanced.With a huge explosion in content, and an increase in advertising clutter, especially online, it is important  to understand what works and what doesn’t, in terms of the advertising creatives. This research paper seeks to understand what combination of advertising formats, whether graphical, or textual, would lead to more engagement from the viewer. To do this, the consumer engagement with different sets of advertising creatives (image heavy, text heavy and balanced) were analyzed through the data received from an eye-tracking experiment.The results obtained from this study are relevant for advertisers, in terms of understanding an optimal textual and imagery mix for their online ads (on platforms such as Facebook, Twitter and Google). Advertisers can use the insights to design advertising creatives, in such a way that they get more engagements from consumers.